PENGARUH PENGGUNAAN BEBERAPA JENIS MEDIA FILTRASI TERHADAP KUALITAS LIMBAH CAIR EKSTRAKSI SAGU (metroxylon sp.) - Sarman Oktovianus Gultom; Trhessya N Mess; Isak Silamba (Agroindustrial Technology, University of Trunojoyo Madura, 2018)
Sago is a carbohydrate-producing plant that is widely found in Papua. The main product of sago plant processing is sago starch which in the extraction process is carried out with the help of water media. Water that has been used in the extraction process of sago starch is generally only disposed of as waste that is not useful, even potentially polluting the environment. Therefore, to improve the quality of liquid waste, filtration needs to be carried out. This study aims to see the effect of several types of filtration media on the quality of sago extraction wastewater. In this study three types of filtration media were used, namely sand (P), coconut fiber (S) and coconut shell charcoal (A) and a combination of sand and coconut fiber (PS), sand and coconut shell charcoal (PA), coconut fibers and charcoal coconut shell (SA). The parameters of the quality of the sago extraction wastewater were observed in total suspended solids (TSS), total dissolved solids (TDS), pH, temperature, odor, and color. The results showed that coconut shell charcoal filtration media was better than the other two types in decreasing TSS and TDS by 17% and 24% respectively. However, if the filtration media was combined, it will produce a better quality of wastewater compared to a single filtration medium (without combination) for all observation parameters. An increase in pH and odorless happened for the wastewater after filtration in all treatments